(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The teaching of Academic English has become increasingly important in modern education due to the growing demand for international communication, academic mobility, and research activities. Traditional methods of language instruction, which primarily focus on grammar translation and teacher centered learning, are no longer sufficient to meet the needs of twenty-first-century learners. Innovative teaching approaches have emerged as effective alternatives that promote student engagement, critical thinking, collaboration, and independent learning. This article examines various innovative approaches used in teaching Academic English and evaluates their effectiveness in improving learners’ academic language skills. The study highlights the role of technology-enhanced learning, flipped classrooms, project-based learning, collaborative learning, and game-based instruction in fostering academic success.